77. Correlations between electrophysiological and clinical changes in spinal surgery. Issue 4 (April 2016) - Giobbe, M.L.; Borio, A.; Marmolino, S.; Faccani, G.; Costa, P.
Abstract : Change in somato-sensory evoked potentials (SSEP) or motor evoked potentials (MEPs) are variably associated with clinical modifications. This study aimed to investigate if neurophysiological changes during IOM are related with clinical modifications in patients underwent spinal surgery. 71 patients that presented neurophysiological changes in somato-sensory evoked potentials (SEPs) or motor evoked potentials (MEPs) during spinal surgery were considered. The pathologies included in the study were: cervical/thoracic myelopathy (27 pts, 38%), spinal cord tumours (31 pts, 44%), scoliosis correction (3 pts, 4%), trauma (7 pts, 10%) and spinal vascular malformations (3 pts, 4%). Clinical outcome, estimated with McCormick scale, was evaluated in the immediate postoperative period and at one month follow-up. Neurophysiological changes were associated to clinical modifications at one month follow-up in 36 patients (51%). When a clinical improvement was observed (19 pts), the percentage of SEPs or MEPs reappearance from basal absence was 42% (8 pts). Contrariwise, evoked potentials disappeared in 65% (11 pts) of observed clinical worsening (17 pts). Neurophysiological modifications in SEPs or MEPS seem to be associated clinical changes in patients submitted spinal surgery.